2020
DOI: 10.1007/s10461-020-02846-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Motivational Interviewing for Antiretroviral Medication Adherence in People with HIV

Abstract: Antiretroviral therapy (ART) for HIV requires strict regimen adherence. Motivational interviewing (MI) can improve ART adherence. MI process studies have rarely focussed on ART adherence. Such studies may facilitate MI modifications to improve outcomes. This study employed a single group pre and post-test design with 62 adults with HIV (16 female; mean age 40 years). Therapist use of MI-consistent (MICO) methods, MI spirit, and client change and sustain talk were coded from an MI session. Relationships were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…This aligns with the theoretical framework of offering youth friendly services, motivational interviewing, and cognitive behavioural therapy to change behaviour. 26,27,28 These findings are consistent with the Thai study that showed the potential of an empowerment programme for youth in improving adherence to ART. 17 The study results showed that young people who never attended the EACGI showed the lowest rates of suppression on the switched regimen.…”
Section: Discussionsupporting
confidence: 87%
“…This aligns with the theoretical framework of offering youth friendly services, motivational interviewing, and cognitive behavioural therapy to change behaviour. 26,27,28 These findings are consistent with the Thai study that showed the potential of an empowerment programme for youth in improving adherence to ART. 17 The study results showed that young people who never attended the EACGI showed the lowest rates of suppression on the switched regimen.…”
Section: Discussionsupporting
confidence: 87%
“…Having these positive outcome expectations is a key factor for promoting health behaviours according to social cognitive theory 31 . The use of motivational interviewing can help identify and improve outcome expectations 32‐35 . This idea is further supported by our finding that many Veterans reported being motivated by provider education about the importance of taking medications and the harmful effects of HCV.…”
Section: Discussionmentioning
confidence: 56%
“…Some studies have failed to show an impact on ART adherence from MI. More research is warranted to investigate non-motivational challenges as adherence is determined by both motivational and non-motivational factors [8]. However, even with some mixed results on efficaciousness, the overall literature indicates MI can have an important impact on behavior change.…”
Section: Introductionmentioning
confidence: 99%